VALIDATION OF SIDDHA PATHOLOGICAL CONCEPTS OF SIRAKAMBAVATHAM AND ITS PARALLEL ANALYSIS WITH CEREBRO VASCULAR ACCIDENTS (STROKE) - Chithra L; Christian G.J; Elansekaran S; Ramamoorthy M (International Journal of Ayurveda and Pharma Research, 2020)
The Siddha system of medicine is widely practiced in South India and consists of an enormous classical literature that emphasize on pathological basis of disease. Contrary to conventional pathological basis of diseases, the Siddha pathology is solely based on the humoral makeup of individuals and rests on the conceptual framework formed by 96 Thathuvams (philosophies). These concepts connect the physical and inert energies of human body facilitating its existence at subtle and gross levels. Sirakkambavatham is one among the 80 Vatha diseases mentioned in the Siddha literature Yugivaithiyasinthaamani. The present literature survey has been conducted to provide an updated integrative framework of information about the pathological concepts of Sirakkambavatham from Siddha literature and its parallel analysis with Cerebrovascular accidents (Stroke).Validating the traditional text in the limelight of modern literature unveils the traditional wisdom of ancient saints of South India and provides a better approach for disease diagnosis, prevention and its management.